Effect of sama vritti pranayama on intradialytic hypertension in patients with chronic kidney disease: a pilot study - Dalvi, Mrudula A.; Afle, Gauri Mayank (International Journal Of Community Medicine And Public Health, 2023)
Chronic kidney disease is identified when the glomerular filtration rate is less than 60 ml per minute/1.73-meter square for a period of greater than or equal to 3 months but with evidence of injury to renal structure. Intradialytic hypertension (IDH) is defined as an increase in the BP, especially systolic BP of >10 mmHg during or immediately after dialysis. Vritti pranayama is a type of pranayama which includes samavritti and visamavritti pranayama. In samavritti pranayama, an attempt is made to achieve uniformity in the duration of all 4 processes of breathing namely, inhalaltion, retention, exhalation and retention A pilot study on 10 patients was conducted on patients with chronic kidney disease having intradialytic hypertension. Samavritti pranayama was performed by the patients for 6 cycles/session 2-3 times/week for four weeks and blood pressure was measured before and after 4 weeks of intervention. The results of the study showed that the mean value of intradialytic systolic blood pressure before the intervention in the 1st week was 181.25 mmHg and that of diastolic was 92.45 mmHg. The mean intradialytic systolic blood pressure after 4 weeks was 161.85 mmHg and diastolic was 84.07 mmHg. This study concluded that there was a significant difference in the intradialytic systolic and diastolic blood pressure after 4 weeks of samavritti pranayama.